2015
DOI: 10.1371/journal.pone.0129820
|View full text |Cite
|
Sign up to set email alerts
|

The rs12526453 Polymorphism in an Intron of the PHACTR1 Gene and Its Association with 5-Year Mortality of Patients with Myocardial Infarction

Abstract: ObjectiveThe rs12526453 (C/G) is a single nucleotide polymorphism in an intron of the PHACTR1 gene (phosphatase and actin regulator 1). The C allele is associated with increased risk of coronary artery disease in an unknown mechanism. We investigated its association with long-term overall mortality in patients with ST-elevation myocardial infarction (STEMI) treated invasively.MethodsTwo independent groups of patients with STEMI were analyzed: a derivation group (n= 638) and a validation one (n=348). Genotyping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In this study, our results further showed that GSDMD expression, an executor of pyroptosis, is significantly increased in gastric mucosa with H. pylori infection, which is in line with the result displayed that GSDMD is drastically decreased in gastric epithelial cells in response to rabeprazole stimulation, a regimen for H. pylori-infectious treatment. What's more, the inappropriate activation of the NLRP3 inflammasome could contribute to the onset and progression of various diseases [38], such as obesity [39], type 2 diabetes [40], inflammatory bowel disease [41], rheumatoid arthritis [42], liver fibrosis [43], Myocardial infarctions [44]. In addition to both NF-KB and SREBP-1c have been reported to regulate NLRPs transcription [17,18,20,45], the further work is required to address the mechanism through which rabeprazole regulated NLRP3, leading to inhibit NLRP3 inflammasome in future work.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, our results further showed that GSDMD expression, an executor of pyroptosis, is significantly increased in gastric mucosa with H. pylori infection, which is in line with the result displayed that GSDMD is drastically decreased in gastric epithelial cells in response to rabeprazole stimulation, a regimen for H. pylori-infectious treatment. What's more, the inappropriate activation of the NLRP3 inflammasome could contribute to the onset and progression of various diseases [38], such as obesity [39], type 2 diabetes [40], inflammatory bowel disease [41], rheumatoid arthritis [42], liver fibrosis [43], Myocardial infarctions [44]. In addition to both NF-KB and SREBP-1c have been reported to regulate NLRPs transcription [17,18,20,45], the further work is required to address the mechanism through which rabeprazole regulated NLRP3, leading to inhibit NLRP3 inflammasome in future work.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al found that cardiovascular mortality was higher in subjects with the rs4977574 GG genotype than in those with other genotypes 96 . The association between four SNPs on chromosome 9p21, CAD, and MI has been replicated several times in multiple populations [97][98][99][100] In patients with MI with ST-segment elevation Szpakowicz et al revealed association between the rs12526453 of the phosphatase and actin regulator 1 (PHACTR1) gene and 5-year mortality 101 . However, in another study, the DIO2 Thr92Ala polymorphism was not related with thyroid parameters, cognitive functioning and health-related quality of life 102 .…”
Section: Discussionmentioning
confidence: 95%
“…It is generally recognized that CAD is a multifactorial disease [ 14 ]. The occurrence and development of CAD are influenced by environmental and genetic factors.…”
Section: Discussionmentioning
confidence: 99%